2019
DOI: 10.1093/pcmedi/pbz018
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of xenografts of urological cancers on chicken chorioallantoic membrane (CAM) to study metastasis

Abstract: Cancer of the urological system commonly occurs in the kidney, bladder, and prostate gland. The clear cell subtype of renal cell carcinoma (ccRCC) constitutes the great majority of kidney cancer. Metastatic ccRCC portends a very poor outcome with no effective treatment available. Prostate cancer is the most common cancer in males in the US. Despite recent advances in selective kinase inhibitors and immunotherapies, the rate of developing new treatment from bench to bedside is slow. A time-consuming step is at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 48 publications
2
51
0
Order By: Relevance
“…Hence, vessel ingrowth 51 as well as tumor metastasis were successfully determined using the CAM-assay 57 allowing a sufficient monitoring of tumor development, regardless of the limited observational time frame. Aside from Hu et al who observed equivalent tumor growth patterns and metastatic behavior for renal carcinoma cells in the CAM-assay and in mice 56 , further working groups were able to demonstrate parallels regarding the tumor size for different tumor entities in comparative experiments 46 , 57 . In our experience, a major disadvantage of experimentation with a chicken model is the very limited commercial availability of chicken specific antibodies.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Hence, vessel ingrowth 51 as well as tumor metastasis were successfully determined using the CAM-assay 57 allowing a sufficient monitoring of tumor development, regardless of the limited observational time frame. Aside from Hu et al who observed equivalent tumor growth patterns and metastatic behavior for renal carcinoma cells in the CAM-assay and in mice 56 , further working groups were able to demonstrate parallels regarding the tumor size for different tumor entities in comparative experiments 46 , 57 . In our experience, a major disadvantage of experimentation with a chicken model is the very limited commercial availability of chicken specific antibodies.…”
Section: Discussionmentioning
confidence: 96%
“…Due to ethical concerns and the occurrence of nonspecific inflammatory reactions after 15 days of incubation 2 , we only evaluated tumor growth in the CAM-assay till day 14 after incubation. However, other working groups have published research evaluating tumors grown in ovo up to day 20 of incubation 56 . Additionally, tumors on the CAM grow much faster than equivalent tumors subcutaneously implanted into mice.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, evaluation of cancer spread beyond the primary lesion using sensitive imaging technologies continues to improve today. In addition to preclinical studies, future work should focus on using the CAM as a platform to graft different primary cell and tissue types, which has already been started 6,24,37 .…”
Section: Discussionmentioning
confidence: 99%
“…Up until now, the most representative models were obtained after intracardiac or intraosseous injection of tumor cells in immunodeficient mice 35 or, as recently reported, in bioengineered mouse models with humanized bones 36 . Recently CAM xenografts from PCa were successfully established 37 . Previous studies on PCa using the CAM were based on visualization of the primary tumor and intravasation process 9 .…”
Section: Igr-cap1mentioning
confidence: 99%
“…In our working group we only evaluated tumor growth till day 14 due to ethical concerns and the occurrence of nonspeci c in ammatory reactions typically starting after 15 days of incubation (27). Nevertheless, other working groups evaluated tumor development till day 20 of incubation (55). Contrarily tumors on the CAM grow much faster than equivalent tumors Finally, as exemplarily shown in Table 1 the costs for a su ciently ingrown tumor suitable for experimentation highlight the signi cantly increased cost e ciency of the CAM-assay compared to rodent experiments.…”
Section: Discussionmentioning
confidence: 99%